Un IDex pour quoi faire ? - Gérald Gaglio; Nathalie Richebé (Revue d'anthropologie des connaissances)
This article seeks to answer the question “what is an IDex for?” from the point of view of the designers and managers of a particular IDex (Aba), and then from that of its beneficiaries. The analysis is based on a qualitative survey that focuses mainly on interviews with “winners” (researchers coordinating funded projects). These were supplemented by interviews with the initiators and managers of the IDex studied and by a documentary analysis. In terms of its governance, this mechanism is part of a broader transformation ambition aimed at establishing itself advantageously in the French RSE landscape. Locally, a dynamic has been attempted to be set in motion by promoting a staircase model: researchers obtain IDex funding for exploratory projects that are deemed original, and then submit to larger “desks”. On the part of researchers, this framework has generally led to appropriation, because, although it is an incentive, it has been malleable (with criteria such as local anchoring and interdisciplinarity) and ultimately not very restrictive (in terms of submission, reporting, use of funding, etc.). Our analysis has led us to identify two registers of appropriation, which combine: a “convinced” register, with an adjustment between the framing of the system and professional convictions, and another register of “professional utilitarianism”. The “staircase model” promoted by the IDex management has, however, been diversified in practice (with the juggling of funding, the funding-relief), and even subverted (stopgap funding). Finally, we stress the flaws in the appropriation of the IDex Aba and the dependence on the original disciplinary affiliation.